(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2017)
هدف البحث إلى التّعرف إلى مستوى جودة الخدمة الدّاخلية والرّضا الوظيفي في منشأة الهوليداي بيتش السّياحيّة في محافظة طرطوس، وكذلك التّعرف إلى دور جودة الخدمة الدّاخلية بأبعادها المختلفة في تحقيق الرّضا الوظيفي لدى العاملين في المنشأة. طبق البحث في العام 2015 على عينة شملت (55) عاملاً وعاملة في المنشأة. ولتحقيق هدف البحث صُممت استبانة تألفت من قسمين؛ الأول تناول الرّضا الوظيفي، وضمّ (23) موزعة والثاني تناول جودة الخدمة الدّاخلية ضم (18) عبارة. توصل إلى عدّة نتائج أهمّها: إن مستوى جودة الخدمات الدّاخلية لدى منشأة الهوليداي بيتش هي بدرجة متوسطة، وأن درجة الرّضا الوظيفي للعاملين عن جودة الخدمات الدّاخلية هي متوسطة، ووجود علاقة ذات دلالة إحصائيّة بين جودة الخدمات الدّاخلية والرّضا الوظيفي للعاملين. كما توصلت النّتائج إلى عدم وجود فروق ذات دالة إحصائياً في إجابات أفراد عينة البحث حول جودة الخدمة الدّاخلية في المنشأة تبعاً لمتغيّر الجنس، ووجود فروق دالة إحصائياً تبعاً لمتغيّر المؤهل العلمي لصالح حملة الدّراسات العليا. وبيّنت النّتائج أيضاً عدم وجود فروق دالة إحصائياً في إجابات أفراد عينة البحث حول درجة الرّضا الوظيفي لدى للعاملين تبعاً لمتغيّري (الجنس، المؤهل العلمي). كما قدّم البحث عدة مقترحات أهمّها: تقديم تسهيلات مرتفعة في الخدمة الدّاخلية، التي سوف تنعكس إيجاباً على رضا العاملين من جهة، وعلى الخدمة الخارجيّة من جهة أخرى. The aim of the research is to identify the level of internal service quality and job satisfaction in the Holiday Beach property in Tartous, as well as to identify the role of internal service quality in its various dimensions to achieve job satisfaction among workers at the facility. The research is applied in 2015 on a sample of (55) employee. To achieve the aim of the research, a questionnaire is designed consisting of two parts; the first dealt with job satisfaction, and included (23) terms, and the second part dealt with the quality of internal service including (18) terms. The research reached several conclusions, including: The level of quality of internal services is a medium degree, and that the degree of job satisfaction for workers about the quality of internal services is medium, and the presence of a statistically significant relationship between the quality of internal services and job satisfaction for workers in the facility. The research also found that there are no statistically significant differences in the answers of the research sample members about the quality of internal service depending on the sex variable, and the presence of statistically significant differences depending on the educational qualification variable for of high studies graduates. Results also showed that there were no statistically significant differences in the research sample answers about the degree of job satisfaction among workers at the facility depending on the variables (sex, educational qualification). The research also made several proposals, including: providing high facilities in the internal service, which will positively reflect on the satisfaction of the employees on the one hand, and on the external service on the other hand.